Character Education for Teenagers Regarding the Dangers of Drug Abuse in Babakan Banten - Susanti, Eka Putri; Firdaus, Anoegrah; Pangestuti, Rinda Siaga; Khatimah, Husnul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research highlights character education's role in preventing teenage drug abuse and addressing the widespread issue and associated risks. Method: Qualitative methods, including workshops and seminars, were employed to promote awareness and understanding within the community. Practical Applications: Integrating drug prevention education into school curricula and community initiatives can effectively mitigate drug-related challenges among teenagers. Conclusion: Character education plays a vital role in combating teenage drug abuse. Integrating drug prevention programs into educational and community settings contributes to a safer and healthier society.